Fârâbî metafiziğinde imkân kavramı - Uyarer, Hatice (My University, 2021)
Fârâbî felsefesinde imkân kavramı, zorunlu ve hakîkî mümkün için kullanılmıştır. Bu çalışma Farabi metafiziğinde; hiyerarşi, yaratma, var olma ve Tanrı’nın ön bilgisi gibi konularla ilgili olması bakımından imkân kavramını ele almıştır. Birincil kaynaklardan yararlanılarak, Fârâbî metinleri incelenmiştir. Sonunda imkânın, metafiziğin kurucu kavramlarından birisi olduğu sonucuna varılmıştır. İmkân; var olan, var olması imkânsız olmayan varlığın en temel kavramıdır. Bu nedenle imkân konusu ele alınarak literatüre katkı sağlamak hedeflenmiştir.

In Fârâbî’s understanding of philosophy the concept of contingency is used for necessity and possibility. As this research takes hierarch, creation, existence, and into consideration within Fârâbî’s metaphysics, we can clearly depict that it addresses the concept of contingency. Fârâbî’s texts are studied and analyzed by referring to primary soucers. The conclusion drawn from the result is that contingency is one of the constitutive concepts od metaphysics. Contingency classifies the ones that exist and the ones wich are not impossible to exist. Fort his reason, what is being aimed at is that the subject of contingency has been made a study of together with in the subject of existence in order to make a contribution to the literatüre.
Keywords: Contingency; Fârâbî; Farabi, M.S. 870-950; Felsefe ve din; Foreknowledge of God; Islamic philosophy; İmkân; İslam felsefesi; Necessity; olasılık; Philosophy and religion; Possibility; Tanrı’nın ön bilgisi Al- Fârâbî; zorunlu